POLITICAL AND ECONOMIC UNFAIRNESS IN HEALTH SYSTEM OF PAKISTAN: A HOPE WITH THE RECENT REFORMS - Shaikh, Shaikh BT; Ejaz, Ejaz I; Achakzai, Achakzai DK; Shafiq, Shafiq Y (Journal of Ayub Medical College Abbottabad, 2013)
Background: For the last few years, Pakistan's health system has faced numerous challenges pertaining to human resource and its deployment, resource allocation among the different tiers of the health care system, infrastructure development and unfair access to care. The enactment of the recent constitutional amendment has made the health system's situation even more uncertain than before. Methods: A detailed literature review was carried out to understand fairness an responsiveness in health systems. The findings of the review were then compiled particularly in the wake ofrecent constitutional amendment defining health sector reforms in Pakistan. Results: Various levels, features and components of health system of Pakistan were looked into in view of understanding the extent of '˜fairness', '˜responsiveness' and '˜adequacy'. Healthcare financing; geographic distribution of health care facilities; human resources in health; access to health services and essential medicines; the allocations to urban and rural segments; and finally understanding the health positioning in national agenda and priorities were examined for this purpose. Conclusions: In the post-devolution scenario, provinces must think systematically how to deal with the capacity issues to manage different components of health care system. Nonetheless, as a country, collective actions would be required to avoid any pitfalls, while approaching Millennium Development Goals by 2015. Keywords: Unfairness, Health system, Devolution, Millennium Development Goals